THEORIES OF MANAGEMENT OF THE RESEARCH ACTIVITY IN THE KNOWLEDGE-DRIVEN SOCIETY AND THEIR APPLICABILITY IN HIGHER EDUCATIONAL INSTITUTIONS: SYSTEMATIC REVIEW - Shykhnenko, Kateryna (Studies in Comparative Education, 2020)
The purpose of the review was to identify the world-recognized management theories that are used to manage the research activity in higher educational institutions and assess the applicability of them in higher educational institutions of Ukraine. This study relied on the methods recommended for feasibility studies. This review utilised qualitative methods in the search and assessment of the relevant studies. Two instruments were used in the study. These were the Critical Appraisal Checklist and the Triangular Assessment Method. The theoretical management concepts such as Total Quality Management, Project Management, the Excellence Model designed by the European Foundation for Quality Management, Balanced Scorecard System, and Organisational Management have been adapted to the purpose of managing research at higher educational institutions. The findings implied that research management could be seen as a dimension of the quality management policy of the higher educational institutions. The study suggests that Organisational Management is quite a blur concept so far which causes misinterpretations and misleadings in terms of both research activity organisation and promotion. It was found that the Total Quality Management and Project Management concepts could be used to manage the research activity at universities in Ukraine. The Balanced Scorecard System concept could also be applicable in Ukrainian higher educational institutions. However, the EFQM Excellence Model and Organisational Management could be partially applicable in Ukraine as they are more commerce-oriented, which seems to be a legislative loophole in Ukraine.